Burden of Cardiomyopathic Genetic Variation in Lethal Pediatric Myocarditis. (6th July 2021) - Kontorovich, Amy R.; Tang, Yingying; Patel, Nihir; Georgievskaya, Zhanna; Shadrina, Mariya; Williams, Nori; Moscati, Arden; Peter, Inga; Itan, Yuval; Sampson, Barbara; Gelb, Bruce D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Acute myocarditis (AM) is a well-known cause of sudden death and heart failure, often caused by prevalent viruses. We previously showed that some pediatric AM correlates with putatively damaging variants in genes related to cardiomyocyte structure and function. We sought to evaluate whether deleterious cardiomyopathic variants were enriched among fatal pediatric AM cases in New York City compared with ancestry-matched controls. Methods: Twenty-four children (aged 3 weeks to 20 years) with death due to AM were identified through autopsy records; histologies were reviewed to confirm that all cases met Dallas criteria for AM and targeted panel sequencing of 57 cardiomyopathic genes was performed. Controls without cardiovascular disease were identified from a pediatric database and matched by genetic ancestry to cases using principal components from exome sequencing. Rates of putative deleterious variations (DV) were compared between cases and controls. Where available, AM tissues underwent viral analysis by polymerase chain reaction. Results: DV were identified in 4 of 24 AM cases (16.7%), compared with 2 of 96 age and ancestry-matched controls (2.1%, P =0.014). Viral causes were proven for 6 of 8 AM cases (75%), including the one DV+ case where tissue was available for testing. DV+ cases were more likely to be female, have no evidence of chronic inflammation, and associate with sudden cardiac death than DV− cases. Conclusions: Deleterious variants in genes related to cardiomyocyte integrity are more common in children with fatal AM than controls, likely conferring susceptibility. Additionally, genetically mediated AM may progress more rapidly and be more severe.